Construction and Validation of Emotional Intelligence Scale for Secondary School Teachers - Antara Dey; Nil Ratan Roy (LED Edizioni Universitarie, 2022)
In this study, we developed and validated a new instrument: an emotional intelligence scale for teachers. This paper focused on the psychometric properties of the emotional intelligence scale for school teachers dealing with adolescent students. The study also validated the tool over 608 secondary school teachers in India. This scale was evaluated using exploratory factor analysis (EFA), confirmatory factor analysis (CFA), Cronbach's alpha, and item-total correlation. Results showed good fit (χ2/df =1085.66, CFI = 0.956, GFI = 0.876, TLI = 0.951, PCFI = 0.860, PNFI = 0.843, RMSEA = 0.06 and SRMR = 0.056) for the five components (Self-Perception, Self-Regulation, Self-Drive, Empathy, Social Motive) of the measurement model. However, 80.18% of the total variance was explained by the factors Reliability (Cronbach alpha = 0.95) and construct validity means convert and discriminant validity was established for a teacher's innovative emotional intelligence scale. Finally, the robust findings indicated that the instrument could be used in further studies in different research areas.